The Impact of Turmeric, Curcuma, and Ginger Feed Additives on the Productivity of Kaur Cattle as a Genetic Resource in Bengkulu - Zulpadly, M. Fiqri; Meitasari, Annisa Diyan (Faculty of Agriculture, 2024)
Kaur cattle, a local breed in Bengkulu, represent a valuable genetic resource that requires preservation and effective utilization to enhance livestock production. Turmeric, curcuma, and ginger are plants known for their essential oils and curcumin content, which offer numerous proven benefits. This study aimed to evaluate the impact of these feed additives on the productivity of Kaur cattle. A quantitative research method employing a completely randomized design was used, consisting of four treatments and four replications. The diet comprised wild grass (10% of body weight) and palm kernel meal in an 80:20 ratio. The treatments were as follows: P0 (control: wild grass and palm kernel meal), P1 (wild grass, palm kernel meal, and turmeric powder Curcuma xanthorrhiza Roxb.), P2 (wild grass, palm kernel meal, and curcuma powder Curcuma longa L.), and P3 (wild grass, palm kernel meal, and ginger powder Zingiber officinale Rosc.). The study involved 16 male Kaur cattle aged 1.5-2 years, with an average body weight of 160-180 kg, observed over 60 days. The variables measured included average daily weight gain, forage consumption, total feed consumption, feed efficiency, and cost efficiency. Data were analyzed using a one-way ANOVA. The results showed that the mean daily weight gain (kg/head/day) was P0=0.352.57, P1=0.472.39, P2=0.502.46, and P3=0.492.88, with no significant differences between treatments. The mean feed efficiency (%) was P0=0.124.44, P1=0.254.71, P2=0.275.22, and P3=0.264.38, also showing no significant differences. The mean cost efficiency for feed use was P0=35,8697.47, P1=34,2817.08, P2=33,2207.39, and P3=35,4107.21, with no significant differences observed. Overall, the addition of turmeric, curcuma, and ginger powders to the feed did not significantly impact the productivity of Kaur cattle.